Effect of Bulking Materials on Composting of Layer Litter (Journal of Environmental Science and Natural Resources, 2015)
The experiment was carried out to examine the possibilities of making compost by using layer litter with different bulking materials and to assess the nutritive value of compost. To fulfill the objectives five treatments were considered e.g., anaerobic composting with layer litter (T1), layer litter with straw (T2), layer litter with tree leaves (T3), layer litter with crop residues (T4) and layer litter with saw dust (T5) under soil surface. The samples from composted materials were collected at 0, 10, 20 and 30 days for proximate analysis. At 0 day of layer litter composting DM content did not vary significantly (p>0.01) var ied in all treatments.. At 10 day of layer litter composting DM content was the highest in T4 (50.0%) and CF content was the highest in T2 (22.2%). CP content remained similar varied in all treatments. At 20 day of layer litter composting DM content was highest in T4 (51.5%), CP content was the highest in T4 (19.5%), CF content was the highest in T2 (18.0%), Ash content was the highest in T4 (18.5%). At 30 day of layer litter composting DM content was the highest in T2 (51.1%) and CP content was the highest in T4 (17.6%). The pH value decreased upto first tendays then gradually increased with the composting period and highest value was obtained by T1 (8.40) then followed by T2 (8.20), T3 (8.15), T5 (8.10) and T4 (8.00) (p